Self-powered, ultraviolet-visible perovskite photodetector based on TiO2 nanorods. Issue 8 (14th January 2016) - Zhou, Hai; Song, Zehao; Tao, Pan; Lei, Hongwei; Gui, Pengbin; Mei, Jun; Wang, Hao; Fang, Guojia
Abstract : A self-powered, ultraviolet-visible perovskite photodetector based on TiO2 nanorods/CH3 NH3 PbI3 heterojunction was reported. Abstract : A self-powered, ultraviolet-visible perovskite photodetector based on TiO2 nanorods/CH3 NH3 PbI3 heterojunction was reported. We found that the device showed good photovoltaic properties with a short-circuit current density of 17.83 mA cm −2, an open-circuit voltage of 0.76 V and a fill factor of 51.34%, leading to a PCE of 6.95%. Based on the wide band gap and the perovskite supporting part of the TiO2 nanorods, the device showed good ultraviolet-visible photo-response characteristics with the responsivity at zero bias reaching ∼0.26 and 0.85 A W −1 at 364 and 494 nm, respectively. These results present potential applications of TiO2 /perovskite photodetectors in ultraviolet and visible regions.